STUDY OF SURFACE CH4 FLUX EMISSION FROM GOSAT SATELLITE DATA OVER SELECTED AGRO-ECOSYSTEMS IN INDIA (International Association of Biologicals and Computational Digest, 2022)
The present study was carried out to characterize and quantify the seasonal behaviour of surface CH4 emissions from L4A product over two selected irrigated agro-ecosystems in India over sub-humid region of Indo-Gangetic Plain (IGP) and semi-arid region of Gujarat Plain and Hills Region (GPHR). Satellite data of Greenhouse Gases Observing SATllite (GOSAT) with L4A data product has been used with a cluster of contiguous grids of 3 x 3 within the Region of Interest (ROI) representing agricultural land uses spread over trans, upper, middle and lower part of IGP for analysis. The seasonal behaviour was studied for three agricultural years of June 2009 to May 2012 through time series plots of monthly means of each ROI. The annual CH4 emission from agricultural region using GOSAT data was found to be about 8-9 Mt CH4 which was about three times higher than reported over rice system in India using sparse ground samplings. The IGP showed the highest annual mean (88.11 mg CH4 d-1m-2) of surface emission in Lower Gangetic Plain Region (LGPR) and the lowest annual mean (7.01 mg CH4 d-1m-2) in Trans-Gangetic Plain Region (TGPR). These sub-humid irrigated agricultural regions with rice-wheat rotation showed substantially higher emissions than those in semi-arid irrigated agriculture (10.38 mg CH4 d-1m-2 to 11.32 mg CH4 d-1m-2) in GPHR. In IGP for an agricultural growing year (June 2009 to May 2010), the mean of CH4 emissions for kharif (June to October) season showed higher emission flux with 51.04 mg CH4 d-1m-2 than in rabi (November to April) Season (14.31 mg CH4 d-1m-2), but coefficient of variation was found to be more in rabi season (77.8%) than in kharif (39.3%) season. In GPHR region for same year, the annual mean of CH4 emissions for kharif and rabi season were 14.26 mgCH4 d-1m-2 and 7.03 mg CH4 d-1m-2, respectively but the coefficient of variation (CV) during kharif are more (30.37%) than in rabi (29.29%).
Keywords: Methane, Kharif, Rabi, GOSAT